2022
DOI: 10.1177/11786302221094418
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Pesticide Residual Levels and Acute Respiratory Infections in Children Under 5 Years of Age: Findings From the Offinso North Farm Health Study

Abstract: Background: Several environmental factors are associated with the risk of acute lower respiratory infections (ALRIs) and upper respiratory infections (URIs) in children under 5 years of age (YOA). Evidence implicating chemical pesticides remains equivocal. There are also no data on this subject in these children in Ghana. This study investigated the association between urinary pesticide residual levels and the risk for ALRIs/URIs in children under 5 YOA. Methods: The participants for this study were from the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The majority of the reviewed studies that provided the rates were between 11 and 20% [ 18 , 19 , 28 , 31 - 34 , 47 ]. Additionally, seven studies reported a prevalence between 21 and 30% [ 7 , 15 - 17 , 23 , 24 , 35 ] and four studies recorded a prevalence between 31 and 40% [ 14 , 36 , 43 , 49 ]. Only one study provided a prevalence between 41 and 50% [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the reviewed studies that provided the rates were between 11 and 20% [ 18 , 19 , 28 , 31 - 34 , 47 ]. Additionally, seven studies reported a prevalence between 21 and 30% [ 7 , 15 - 17 , 23 , 24 , 35 ] and four studies recorded a prevalence between 31 and 40% [ 14 , 36 , 43 , 49 ]. Only one study provided a prevalence between 41 and 50% [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the side effects of deltamethrin are allergic skin reactions and respiratory tract irritation. The relationship between the use of mosquito nets and the incidence of ARI is the effect of the chemicals used on the mosquito nets (Akyeampong et al, 2022).…”
Section: Acute Respiratory Infections (Ari)mentioning
confidence: 99%
“…However, prenatal, perinatal or postnatal exposure to DDE was not associated with respiratory infections ( 136 , 137 ) or levels of lymphocytes and monocytes ( 137 , 138 ) while it was inversely related with circulating eosinophils ( 138 , 139 ). Conversely, in Ghana, a significant association between DDE and other pesticides and increased low respiratory infections in children aged 2 to 5 years was described ( 140 ).…”
Section: Gut Microbiotamentioning
confidence: 99%